(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Dental caries is influenced by a complex interplay of genetic and environmental factors, including dietary habits. Previous reports have characterized the influence of genetic variation on taste preferences and dietary habits. The earliest references to the connection between sugar and dental caries dates back to the middle of the fifteenth century, when sugar was a scarce luxury enjoyed only by nobility. Queen Elizabeth in 1598 was noted by a German traveler named Hentzer to have black teeth. It was attributed by Hentzer to her high sugar consumption.